Women’s Perceptions Of Glass Ceiling In The Accounting Profession In Indonesia - Khodijah, Amalia Siti; Pekerti, Retno Dyah; Rahmayanti, Anggraeni Anisa Wara (Journal of Accounting Science, 2024)
General Background: The glass ceiling remains a significant issue in the accounting profession, reflecting persistent gender inequality despite women constituting a large proportion of the workforce. Specific Background: In Indonesia, the phenomenon is exacerbated by cultural and structural barriers that hinder women’s progression into leadership roles. Previous studies have primarily focused on developed countries, leaving a gap in understanding within developing nations like Indonesia. Knowledge Gap: There is limited empirical evidence on how professional women in developing countries perceive the glass ceiling and the factors contributing to it. Aims: This study aims to explore women’s perceptions of the glass ceiling in the Indonesian accounting profession and identify demographic, cultural, and structural factors influencing these perceptions. Results: The study found that perceptions of the glass ceiling are significantly affected by bias in performance evaluations, structural barriers like lack of mentoring, and cultural influences from male leaders. Marital status and having children also play critical roles, with single women and those with children more likely to perceive a glass ceiling. No significant difference was found between public and private sector accountants in this regard. Novelty: The research provides unique insights into the interplay of cultural and structural factors in a developing country context, highlighting the specific challenges faced by Indonesian women accountants. Implications: These findings can inform companies and policymakers to devise strategies to mitigate gender biases and support women’s career advancement. By addressing the identified barriers, organizations can retain talented female employees and enhance gender equality in leadership positions.